Does The Relationship between Profitability, Liquidity, and Leverage Toward Firm Value Get Tempered by Dividend Policy? - Mudjiono, Arif; Osesoga, Maria Stefani (The Indonesian Journal of Accounting Research, 2023)
This research aims to acquire empirical data on the relationship between profitability, liquidity, leverage, and firm value, with dividend policy as a moderating factor. The firm value is significant to creditors and investors because it may be used to gauge a company's capacity to generate profits. Tobin's Q is used in this study to calculate the firm value. A purposive selection technique was utilized to choose the 36 manufacturing companies listed on the IDX throughout 2018–2020, and the moderated regression analysis technique was employed to examine the data. According to the study's findings, profitability has a large positive impact on company value when dividend policy is taken into account, however, liquidity and leverage do not have significant effects. We discovered that businesses with a high firm value made the best use of their resources and could greatly boost production, allowing them to disperse their profits as dividends.